EVALUASI KINERJA PENYULUH BP3K DALAM BIDANG PETERNAKAN DI KECAMATAN PINELENG KABUPATEN MINAHASA - Polohindang, Astrid F; Sondakh, B F.J; Lainawa, J; Tumewu, J M (Universitas Sam Ratulangi, 2016)
ABSTRACT PERFORMANCE EVALUATION OF THE FIELD FARM EDUCATOR IN PINELENG DISTRICT PINELENG OF MINAHASA REGENCY. The purpose of this study was to determine the performance of field farm educator and to know the success of the field farm educator at Pineleng district of Minahasa regency. Respondents were applied by survey method at 1 supervisor, 4 field farm educators and 30 selectedÂ farmers as targets of counseling. Data were collected by interview, observation and documentation. Sources of data were including primary data in the form of extension internal program, age, education, experience, and the number of dependent family. External extension factors were involving Â infrastruc-ture, government policies, the intensity of illumination, and the distance of field farm educator residence. The second primary data were taken regarding the indicators of appraisal extension educator office. Secondary data were obtained from agencies associated with this study, such as the BP3K office of the Pineleng district and Pineleng district office. Data analysis was using qualitative deskriprif. The analysis showed that the internal and external factors affecting one to each other of the performance of the field farm extension of educators. Extension performance appraisal done by superiors to field farm educator assessment itself indicated good category. This good category indicated that from nine assessment indicators, seven of them were done by field farm educators. Field farm educators were not optimal in doing extension because the compiled program did not reach the target. In conclusion internal and external factors influencing the extension performance of field farm educators, in the judgment of superiors are in accordance with the duties and functions of each field farm educator. On the basis of this study, the result of the extension was not optimal because more farmers did not participate and achieve in extension and the planned program objectives of the field farm educators.